Предмет: Алгебра, автор: SuperSultik11

Решите уравнение!
НАЧИНАЯ С №648

Приложения:

Ответы

Автор ответа: IvanTkachuk
2
648. -7- 2(5x-6) = -2
        -7- 10x + 12 = -2
        -10x = -2 + 7 - 12
        -10x = -7
        x = -7/(-10)
        x = 0,7
649. -2 = -9 - 2(-2x+1)
        -2 = -9 + 4x - 2
        -2 + 9 + 2 = 4x
         9 = 4x
         x = 9/4
         x = 2,25
650. 10 - 2(-x - 7) = 9
        10 + 2x + 14 = 9
         2x = 9 - 14 - 10
         2x = 15
         x = 15/2
         x = 7,5
651. 8 - 4(-7x + 8) = 4
        8 + 28x - 32 = 4
        28x = 4 - 8 + 32
        28x = 28
        x = 1
652. 1 - 6(2x - 3) = -2
        1 - 12x + 18 = -2
        -12x = -2 - 1 - 18
        -12x = -21
         x = -21/-12
         x = 1,75
653. 10 + 9(-10-9x) = 8-x
        10 - 90 - 81x = 8 - x
         -81x + x = 8 - 10 + 90
         -80x = -72
          x = -72/-80
          x = 0,9
654. -1 + 8(7-6x) = 2x + 6
         -1 + 56 - 48x = 2x + 6
         -48x - 2x = 6 + 1 - 56
          -50x = -49
           x = -49/-50
           x = 0,98
655. -2 + 3(1 + 2x) = -2x + 3
        -2 + 3 + 6x = -2x + 3
        6x + 2x = 3 + 2 -3 
        8x = 2
        x = 2/8
        x = 0,25
656. -3x + 4 = -10 + 5(-7 - x)
        -3x + 4 = -10 -35 - 5x 
        -3x + 5x = -10 - 35 + 4
        2x = -41 
        x = -41/2
        x = 20,5
657. 3x - 10 = 2 + 6(5 + 4x)
        3x - 10 = 2 + 30 + 24x
        3x - 24x = 2 + 30 + 10
        -21x = 42
        x = -2
658. 5x - 4 = 4 - 3(5 - 2x)
        5x - 4 = 4 -15 + 6x 
        5x - 6x = 4 - 15 + 4
        -x = -7
         x = 7
659. 4 - 2(5 + 4x) = -x + 1
        4 - 10 - 8x = -x + 1
        -8x + x = 1 - 4 + 10
        -7x = 7
        x = -1
660. 10 - 3(1 - 7x) = -4x - 8
        10 - 3 + 21x  = -4x -8
        21x + 4x = -8 - 10 + 3
        25x = -15
        x = -6
661. -1 - 4(-7 + 8x) = -2x - 6
        -1 + 28 - 32x = -2x - 6
        -32x + 2x = -6 + 1 - 28
        -30x = -33
        x = 1,1
662. 5(5 + 3x) - 10x = 8
        25 + 15x - 10x = 8
        5x = 8- 25
        5x = -17
        x = - 3,4
663. 4(7 + x) - 3x = 7
        21 + 4x - 3x = 7
        x = 7 - 21
        x = -14
664. 7(-5 + 3x) + 4x = 9
        -35 + 21x + 4x = 9
        25x = 9 + 35
        25x = 44
        x = 1,76

Похожие вопросы